Import Controls on Foreign Oil: Comment - Amacher, Ryan C.; Tollison, Robert D.; Willett, Thomas D. (American Economic Review, 2016)
The question of whether controls on the importation of foreign oil into the United States should take the form of tariffs or quotas has been a topic of recent public debate and investigation bv econonmists. Under static competitive conditions it is well known that equivalent tariffs and quotas can be constrtucted. Hence in this context, there is no choice to be mlade on economic efficiency grounds.' Hlowever, in a recent isstue of this Review, George Hay poinlts out that the actual market for oil in the United States differs fromii the required textbook conditions for equivalence. Under the U.S. oil import program which prevailed until recentl-, each refiner's quota for inmport of foreign oil is a positive function of his refinery input. Since import tickets are allocated free of charge, rather than auctioned, the form of the quota lowers the marginal cost of domestic refiners. Hay goes on to show that when combined with other static competitive assumptions, this quota mechanismi could generate greater consumer benefits in terms of lower prices than would an equivalent tariff (equivalent in the sense that the same percentage of imports is admitted).2 Hay expresses a preference for tariffs in a real world context and warns that his analysis of the price effects of the U.S. oil quota system holds only under very restrictive conditions. However, he does not address what is perhaps an even more important deviation of the domestic oil industry from the standard textbook model: crude oil production in the United States was limited in the major producing states by regulatory commissions that practiced market demand prorationing under the old oil quota program. Under this system, an-y price set by the industry is ratified by the commissions by limiting production to a level that will not result in the accumulation of undesired inventories.' We are not addressing the issue of the level of price in the oil industry in this paper. Rather, we wish to review the effects of tariffs and quotas on resource allocation, an issue which Hay omits from his analysis; and, for this purpose we make use of the simple model of a profit-maximizing monopolv as a characterization of the domestic oil industry. The assumption of profit maximiza-